Pengaruh Video Dan Simulasi RJP Terhadap Tingkat Pengetahuan Dan Sikap Atlet Sepatu Roda Kota Malang - Wenny Rasmawati Simamora; Supriyadi Supriyadi; Erianto Fanani; Marji Marji (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Current data shows that most cases of Out-of-Hospital Cardiac Arrest or OHCA occur outside health facilities, and the mortality rate is almost 90%. In addition, victims with indications of OHCA experience a decrease in survival rate of 7-9% every minute if they do not receive cardiopulmonary resuscitation. Athletes are a population that has a high potential for experiencing or experiencing OHCA. The importance of this research was to determine the effect of providing videos and simulations of Cardiopulmonary Resuscitation (RJP) on the level of knowledge and attitudes of roller skating athletes in Malang City. The method used is Quasi Experimental Research with a pre test and post test control group design approach. The instrument used in this research was a questionnaire to measure the level of knowledge and attitudes about Cardiopulmonary Resuscitation. The results of the study showed that there was a positive influence from providing videos and simulations of Cardiopulmonary Resuscitation (CPR) on increasing the level of knowledge and attitudes in athletes (with a p-value <0.05). This shows that the learning approach using videos and simulations is effective in improving athletes' understanding and attitudes regarding Cardiopulmonary Resuscitation.